2014
DOI: 10.1111/fare.12087
|View full text |Cite
|
Sign up to set email alerts
|

Family Coaching: An Emerging Family Science Field

Abstract: Although there is a rich history of collaboration and distinction among family practitioners, to remain progressive, the domains of family practice must continue to evolve based on the current practices of family professionals. Recently, family coaching (FC) has captured the professional attention of practitioners as another collaborative yet distinct field in family science. FC seeks to foster the achievement of family-identified goals through a process-driven relationship between a family and professional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This study found that social workers are interested in receiving coaching training and feel that it is important for coaches to be credentialed. This is consistent with Allen and Huff's (2014) findings that family professionals are interested in receiving coach training and they view coaching as an up-and-coming approach to serving families. As a participant that had never heard of coaching, but recognised the strategies of coaching as being the 'essence what social workers do', it is natural that social work training programmes be more widely spread among universities and social work programmes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that social workers are interested in receiving coaching training and feel that it is important for coaches to be credentialed. This is consistent with Allen and Huff's (2014) findings that family professionals are interested in receiving coach training and they view coaching as an up-and-coming approach to serving families. As a participant that had never heard of coaching, but recognised the strategies of coaching as being the 'essence what social workers do', it is natural that social work training programmes be more widely spread among universities and social work programmes.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, research suggests that coaching has positive effects, such as higher levels of goal attainment among clients, stressing the importance of having an evidence-based approach when it comes to the use of coaching (Grant, 2008). The conversation of coaching families is also addressed in family science literature; there is growing support that coaching families is an effective approach to serving families and the practice is rising in popularity among family practitioners (Allen, 2013;Allen & Huff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Family coaches utilize a strengthsbased, solution-focused process to help individuals and families strengthen their relationships and reach goals set by them (Kovacs, 2012). In family life coaching, the client is viewed as an expert in his or her life, and the process of coaching is one of collaboration between coach and client (Allen, 2013;Allen & Huff, 2014). In addition, the role of the coach may change with the family's needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coaching has become a wide-spread phenomenon, used in many fields and diverse practices. However, there is a deficit of research and professionalism of coaching, especially family life coaching (Allen & Huff, 2014 greatly, influencing the training and credentialing needed. To ensure quality in the area of family life coaching, where the coach may be an expert as well as a guide, this trend necessitates further guidelines and research on the relationship between the coach and client, as has already occurred in other fields.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation